Władysław Stanisław Reymont i czeskie reymontiana (Szkic do portretu z ułamków) - Kardyni-Pelikánová, Krystyna (Slavia Occidentalis, 2014)
This article endeavors to register the Czech reception of works by W. St. Reymont, interpreted from various perspectives: the journalistic, the critical, and the literary-scholarly. The author demonstrates that the journalistic and critical sources were often colored by Polish criticism and assumptions generally accepted there, while the literary-scholarly writings were adapted to literary research paradigms embraced by individual scholars. The last part brings attention to the previously undisclosed literary dialogue that V. Martínek, an author of Czech regional prose carried on with Reymont. The entire work is supplemented with a selected bibliography of Czech works about Reymont.